Dry eye syndrome-related quality of life in glaucoma patients - Rossi, Gemma Caterina Maria; Tinelli, Carmine; Pasinetti, Gian Maria; Milano, Giovanni; Bianchi, Paolo Emilio (European journal of ophthalmology, 2009)
To verify the presence of dry eye syndrome (DES) in treated patients with glaucoma and to analyze DES's impact on the patients' quality of life (QOL) versus the control group. In this observational cross-sectional study, 61 patients were enrolled at a clinical practice. Patients were divided into three groups by number of glaucoma drops instilled per day (G1=1 drop/day, G2=2 drops/day, G3=3 drops/day). A control group of 20 subjects was also selected (G0). All subjects were submitted to a complete ocular examination (including tear function and ocular surface status) and completed the 25-item National Eye Institute Visual Function Questionnaire (NEI-VFQ), Glaucoma Symptom Scale (GSS) questionnaire, and Ocular Surface Disease Index (OSDI). DES was defined as presence of punctate keratitis and decreased break-up time. Statistical analysis was performed applying the Kruskal-Wallis analysis of variance and Mann-Whitney U tests (to compare median values between groups) as well as the chi2 and Fisher test (to verify significant differences). A total of 40% of G3 and 39% of G2 patients presented DES versus 11% of G1 and 5% of G0 (p=0.01). QOL was significantly influenced and altered (NEI-VFQ 25 total mean and GSS total mean and symptoms average: p=0.0085, p=0.006, and p=0.03, respectively). OSDI pointed out differences by group: 26% of G2 and 15% of G3 presented moderate OSDI and 15% of G3 and 8.7% of G2 severe OSDI (p>0.05). Patients with topically treated glaucoma present DES more often than a similar control group (p=0.01). The presence of DES negatively influences the patient's QOL. The patients with glaucoma's ocular surface status should be evaluated regularly to ensure the timely detection and treatment of pathologic signs on the ocular surface.